Dielectric permittivity of C-S-H. (July 2023) - Ait Hamadouche, Sofiane; Honorio, Tulio; Bore, Thierry; Benboudjema, Farid; Daout, Franck; Vourc'h, Eric
Abstract: As a porous hydrophilic phase, C–S–H is expected to exhibit a frequency-dependent dielectric response. This C–S–H property remains unknown, despite the importance of dielectric assessment for non-destructive evaluation of concrete. This study adopts a multiscale approach to estimate the complex dielectric response of C–S–H over the 0 to 1000 GHz frequency range. We perform molecular dynamics simulations to compute the frequency-dependent dielectric response of water in C–S–H from the polarization correlation formula. We consider pore sizes covering the range associated with interlayer and gel pores in C–S–H. The dielectric response obtained is anisotropic and pore size dependent, as expected in layered materials. The results at the molecular scale are then used as inputs in a homogenization model to estimate the dielectric permittivity of C–S–H gel, which we compare with estimations obtained from inverse analysis based on experiments. Our results are a valuable input for multiscale modeling of non-destructive testing and evaluation in cement-based materials.